Evaluasi Terhadap Fasilitas dan Aksesibilitas Bagi Wisatawan Penyandang Disabilitas (Wheelchair) Yang Berkunjung Di Desa Wisata Penglipuran, Bali - Aprisa, Ega; Nugroho, Saptono (JURNAL DESTINASI PARIWISATA, 2024)
Facilities comprise all or part of the infrastructure and amenities in buildings and their surroundings to be accessed and utilized by everyone, including persons with disabilities and the elderly. This study aims to evaluate the existing condition of facilities and accessibility for tourists with disabilities (wheelchair users) by analyzing the availability of related facilities in Penglipuran Village as a case study. The research methodology employed is a qualitative approach through in-depth interviews with operational management, direct observation, and documentation of existing facilities. The research findings indicate that facilities and accessibility for tourists with disabilities (wheelchair users) in Penglipuran Village are still inadequate. There are constraints in accessibility in several areas of the village, particularly in residents' houses serving as dining or resting places. Overall, limited accessibility hampers the participation of tourists with disabilities in exploring the entire village area, interacting with local communities, and enjoying some experiences offered by Penglipuran Village. This research provides significant benefits to various stakeholders, including the government, tourism object managers, communities, and tourists with disabilities themselves, to make improvements and enhancements to facilities in line with the needs of tourists with disabilities. Keywords: evaluation; facilities; accessibility; tourists with disabilities.